Myocardial perfusion reserve index during adenosine stress magnetic resonance for the detection of coronary artery disease: ready for prime time? - Korosoglou, Grigorios; Katus, Hugo (Journal of thoracic disease, 2013)
Myocardial perfusion reserve index during adenosine stress magnetic resonance for the detection of coronary artery disease - ready for prime time?
Gesehen am 17.11.2021